1995
DOI: 10.1002/jbt.2570100503
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phenobarbital and the peroxisome proliferator ciprofibrate on γ‐glutamyltranspeptidase activity and leukotriene C4 concentration in cultured rat hepatocytes

Abstract: Peroxisome proliferators induce hepatocellular carcinomas in rodents by an unknown mechanism. gamma-Glutamyltranspeptidase (GGT), a biochemical marker for identifying putative preneoplastic lesions in the liver, is highly expressed in phenobarbital (PB)-promoted altered hepatic foci but not in those promoted by peroxisome proliferators. One of the substrates of GGT is the eicosanoid LTC4. Because peroxisome proliferators and PB have differing effects on eicosanoid metabolism in vivo, we hypothesized that PB wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1996
1996
2003
2003

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…studies (Hong et al, 1995;Leung and Glauert, 19961, the addition of ciprofibrate to the cultures lowered the concentrations of PGEz, PGFza, and LTC, . The addition of eicosanoids in addition to ciprofibrate restored their concentrations (Fig.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…studies (Hong et al, 1995;Leung and Glauert, 19961, the addition of ciprofibrate to the cultures lowered the concentrations of PGEz, PGFza, and LTC, . The addition of eicosanoids in addition to ciprofibrate restored their concentrations (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Peroxisome proliferators induce increased expression of several genes, including the peroxisomal P-oxidation pathway and the cytochrome P-450 4A family, which metabolize lipids, including eicosanoids and their precursor fatty acids (Brass and Ruff, 1991;Capdevila et al, 1992). We previously found that the peroxisome proliferator ciprofibrate decreases the concentration of several eicosanoids in rat liver and in cultured hepatocytes, including prostaglandins E, and Fa, (PGE, and PGF2,) and leukotriene C, (LTC,); Hong et al, 1995;Wilson et al, 1995;Leung and Glauert, 1996). The relationship of these decreased eicosanoid concentrations to the development of hepatic tumors is unclear, since promotion…”
mentioning
confidence: 99%
“…The fact that some hepatoma cells can produce α‐foetoprotein suggests that malignant transformation is frequently associated with a change of cells towards the immature state, which usually corresponds to a certain developmental stage of the foetus. At the same time, the increase of γ‐glutamyl transpeptidase activity and heat‐resistant alkaline phosphatase proportion are the specific properties related with hepatocyte malignancy (Hong et al . 1995; Lu et al .…”
Section: Discussionmentioning
confidence: 99%
“…The fact that some hepatoma cells can produce a-foetoprotein suggests that malignant transformation is frequently associated with a change of cells towards the immature state, which usually corresponds to a certain developmental stage of the foetus. At the same time, the increase of g-glutamyl transpeptidase activity and heat-resistant alkaline phosphatase proportion are the specific properties related with hepatocyte malignancy (Hong et al 1995;Lu et al 1997), while the increase of alkaline phosphatase activity is the marker of hepatoma differentiation (Asmah et al 1994). Our results show G-Rh 2 markedly increased albumin secretion and alkaline phosphatase activity, while strikingly decreased a-foetoprotein secretion, g-glutamyl transpeptidase activity and heat-resistant alkaline phosphatase proportion.…”
Section: Discussionmentioning
confidence: 99%